Is subsurface geophysics as seismic and acoustic investigations a rescue to groundwater flow inversion? - Delay, Frederick; Mari, Jean-Luc; Porel, Gilles; Chabaux, François; Ackerer, Philippe (Comptes Rendus. Géoscience)
Understanding subsurface flow, especially in partly karstified rock formations mainly housing water through a few preferential pathways, is still challenging. This point is the consequence of the poor accessibility of the subsurface and lack of accurate depictions of water bearing bodies and distributions. This notwithstanding, highly-resolved geophysical investigations bring new images of the subsurface.A 3-D seismic survey with shots and wave monitoring at the surface is carried out over a subsurface karstified reservoir located at the Hydrogeological Experimental Site (HES) of the University of Poitiers (France). Processing the 3-D data, in association with wave velocity calibration from vertical seismic profiles (VSP) recorded via geophones in wells, renders a 3-D velocity block. The velocity block is then converted into pseudo-porosity values revealing three high-porosity, presumably water-productive, layers, at depths of 35–40, 85–87, and 110–115 m.In addition, full wave acoustic logging (FWAL) can detect, close to wells, porous or open bodies that are too small for being captured by the spatial resolution of 3-D seismic images. A FWAL can also confirm or invalidate data from VSP recorded via hydrophones.The block of pseudo-porosities is compared to a different representation of the subsurface in the form of hydraulic conductivity distributions (or hydraulic diffusion) obtained by slug tests or by inversion of transient interference testing between wells. The inverted hydraulic conductivity maps do not match up the distribution of porous bodies identified by seismic data. This poses the question of guiding conventional inversions on the basis of a prior guess as the subsurface structure obtained via geophysical investigations.